2019
DOI: 10.3389/fpls.2019.01160
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Splicing Quantitative Trait Loci (sQTLs) in Diverse Ecotypes of Arabidopsis thaliana

Abstract: Alternative splicing (AS) of pre-mRNAs contributes to transcriptome diversity and enables plants to generate different protein isoforms from a single gene and/or fine-tune gene expression during different development stages and environmental changes. Although AS is pervasive, the genetic basis for differential isoform usage in plants is still emerging. In this study, we performed genome-wide analysis in 666 geographically distributed diverse ecotypes of Arabidopsis thaliana to identify genomic regions [splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The functional impact of genetic variations in shaping AS events with stress-adaptive consequences has also been revealed in plants. For example, microsatellites are involved in modulating AS of miRNA genes under different stress conditions [ 178 ], and ‘splicing QTLs’ (sQTLs) potentially regulate AS of various stress-responsive genes [ 179 ]. However, the significance of microsatellites and sQTLs in regulating AS for rice stress tolerance has yet to be determined.…”
Section: Future Outlook For Research On As In Rice Stress Responsesmentioning
confidence: 99%
“…The functional impact of genetic variations in shaping AS events with stress-adaptive consequences has also been revealed in plants. For example, microsatellites are involved in modulating AS of miRNA genes under different stress conditions [ 178 ], and ‘splicing QTLs’ (sQTLs) potentially regulate AS of various stress-responsive genes [ 179 ]. However, the significance of microsatellites and sQTLs in regulating AS for rice stress tolerance has yet to be determined.…”
Section: Future Outlook For Research On As In Rice Stress Responsesmentioning
confidence: 99%
“…These differences suggest that the mechanism of splice site recognition may differ between plants (intron definition) and animals (exon definition) (Barbazuk et al ., 2008). Although many studies on AS are based on expressed sequence tags (ESTs) and cDNAs in plants, only a few studies focus on AS variations at the plant population level (Chen et al ., 2018; Khokhar et al ., 2019). With advancements in next‐generation sequencing technology, it is feasible to obtain RNA‐seq datasets for AS analysis, but it is challenging to accurately determine and quantify AS due to short reads and the complexity of splicing when evaluating a large population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study utilized the same RNA-Seq data from the 1001 genome project and carried out isoform-based splicing QTL analysis 35 using sQTLseekeR 36 based UlfasQTL 37 analysis and concluded that majority of splicing variation in Arabidopsis is due to trans QTL [35][36][37] . This finding is in contrast to our current studies as well as earlier genetic studies 38 that argued for cis-regulatory variation as primary determinants of splicing.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 4. Comparison the of GWAS results between isoform-based approach (Khokhar et al, 2019) and our approach, for the same genes. Supplementary Table 5.…”
Section: Author Contributionsmentioning
confidence: 99%